Automated Production of [68Ga]Ga-Desferrioxamine B on Two Different Synthesis Platforms - Martin Kraihammer; Miloš Petřík; Christine Rangger; Michael Gabriel; Hubertus Haas; Bernhard Nilica; Irene Virgolini; Clemens Decristoforo (Pharmaceutics, 2024)
Background/Objectives: PET imaging of bacterial infection could potentially provide added benefits for patient care through non-invasive means. [68Ga]Ga-desferrioxamine B—a radiolabelled siderophore—shows specific uptake by human-pathogenic bacteria like Staphylococcus aureus or Pseudomonas aeruginosa and sufficient serum stability for clinical application. In this report, we present data for automated production of [68Ga]Ga-desferrioxamine B on two different cassette-based synthesis modules (Modular-Lab PharmTracer and GRP 3V) utilising commercially obtainable cassettes together with a licensed 68Ge/68Ga radionuclide generator. Methods: Quality control, including the determination of radiochemical purity, as well as a system suitability test, was set up via RP-HPLC on a C18 column. The two described production processes use an acetic acid/acetate buffer system with ascorbic acid as a radical scavenger for radiolabelling, yielding ready-to-use formulations with sufficient activity yield. Results: Batch data analysis demonstrated radiochemical purity of >95% by RP-HPLC combined with ITLC and excellent stability up to 2 h after synthesis. Specifications for routine production were set up and validated with four masterbatches for each synthesis module. Conclusions: Based on this study, an academic clinical trial for imaging of bacterial infection was initiated. Both described synthesis methods enable automated production of [68Ga]Ga-desferrioxamine B in-house with high reproducibility for clinical application.